Reply to 'Religious Devoutness Construed as Pathology' by Bartholomew and O'dea - Zablocki, Benjamin David (The international journal for the psychology of religion, 1998)
There has arisen an unfortunate polarization between proreligious and antireligious scholars of religion. In identifying with the former, the Bartholomew and O'Dea article fails to note the truth does not lie in one or the other option. There is a need to comprehend how medicine and psychiatry can constructively contribute to understanding religious phenomena rather than discount them arbitrarily. William James, Marc Galanter, and Julius Rubin are given as examples of this more constructive approach.